Pengembangan Asesmen Kinerja Inquiry Lesson Pada Topik Permasalahan Biologi Abad 21 Siswa SMA - Nadia Zahra; Ana Ratna Wulan; Yanti Hamdiyati (Universitas Pendidikan Mandalika, 2023)
This study aims to produce research products in the form of recommendations for 21st-century competency performance assessment instruments in inquiry lesson skills on 21st-century biological problems. Based on indicators of inquiry lesson Wenning (2012). The study used a mixed method with ten students in class XII as the subject of a high school in Serang. The instrument was analyzed by testing its validity and reliability with Aiken's formula. The result of the validity test with Aiken's formulation was 0.66, which showed that the instrument could be said to be valid. For reliability based on the ICC test, the result was 0.897, and it can be interpreted that the inquiry lesson performance instrument has high reliability. With these findings, teachers can use the inquiry assessment instrument to assess students' inquiry lesson skills.